Pengembangan Aplikasi Perangkat Bergerak Pendampingan Difabel Berbasis Lokasi (Studi Kasus: Pusat Studi Dan Layanan Disabilitas Universitas Brawijaya) - Muh. Fadhil Fathi Rizal; Agi Putra Kharisma; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Disability, disability, or self-limitation is a term that encompasses disruption, limited activity, andrestrictions on participation. In the Ministry of Social Affairs letter number: B.74 / Ministry of SocialAffairs / RS. Set.KS / ks.02 / 09/218 dated 12 Sepetmeber 2018 concerning Disability Assistance Staff.The task of the companion is that persons with disabilities are to ensure that handling and escort arecarried out optimally so that they will be able to meet the basic needs of persons with disabilities onthe condition that the companion must fulfill the requirements. Urgent assistance underpins thedevelopment of using location-based service methods. In this case location-based services are neededso that persons with disabilities who need assistance in the near future can find a companion inaccordance with the location closest to him so that it does not take too long, therefore location-basedservices are needed to assist this process. From the results of excavation needs obtained 2 types ofactors namely the disabled and companion. The application was developed with a Model-View-Controller (MVC) architecture and data storage using the Firebase service with the results of allfunctional tests successfully implemented with an average value above 80% which means it can beaccepted by the user, and can run on the Android operating system with a minimum version SDK 21through 29.